Case Report: Successful Treatment of Kaposi’s Sarcoma With Anlotinib in an HIV-Negative Patient After the Treatment of Drug Reaction With Eosinophilia and Systemic Symptoms Accessory Tragus - Lin, Min; Luo, Renwei; Zhang, Peng; Xiao, Zhixun; Gong, Ting; Ji, Chao (Frontiers in Medicine, 2022)
Kaposi sarcoma (KS) is a neoplasm derived from endothelial cells and is associated with HHV-8(human herpesvirus-8) infection. It is mostly seen in patients suffering from AIDS and/or chronic immunosuppression. Currently, systemic chemotherapy is the treatment of choice in the advanced KS, although there is no consensus in treatment. In this case, a man in his 80s with a history of psoriasis developed multiple painful dark purple nodules on the trunk and extremities during a DRESS treatment. Kaposi's sarcoma was confirmed by the skin biopy and the immunohistochemical staining demonstrated positivity for HHV-8. Whereas the anti-HIV test was negative. The patient then received anlotinib, a tyrosine kinase inhibitor for 4 month. At present, his skin lesions subsided, leaving dark brown pigmentation. This case indicates that anlotinib may be a potential therapy for Kaposi's sarcoma.